The Belt and Road Initiative: Catalyzing Human Capital Development and Technological Innovation for Sustainable Growth - Aamir Shahzad; Hamza Rashid; Syed Mudasser Abbas (China Quarterly of International Strategic Studies)
Belt and road initiative (BRI) is a comprehensive megaproject launched in 2013 by China to realize global connectivity, particularly in infrastructure, trade, and investment of the participating countries. This conceptual review paper examines the BRI’s role as a catalyst for poverty alleviation through its focus on human capital development (HCD) and technological innovation. In the context of the BRI projects, people-to-people exchanges, knowledge transfer, and various skill-building initiatives result in sustainable economic growth in the participating countries. The paper also examines the BRI’s role in driving technological development through investing in research and development (R&D) that ultimately leads to technology diffusion to modernize industries and reduce poverty. It also examines the interaction between human capital and technology as a cyclical relationship; these two complement each other in the cycle of productivity and inclusive development of an economy. A three-pillar model is also presented in the study to support the proper utilization and implementation of the BRI projects and maintain sustainability for inclusive development.